EXPLORING EMOTIONAL INTELLIGENCE DIFFERENCES BETWEEN ATHLETES AND NON-ATHLETES IN DELHI NCR SCHOOLS - Beniwal, Shweta; Dev Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this present research is to attempt to examine the varying levels of EI of athletes and non-athlete school students in the Delhi NCR government and public schools. The study focuses on the effects of participation in sporting activities on EI and interaction between the two variables as moderated by gender and school type. This study used comparative cross-sectional research design and involved 500 students of 14 — 18 years old participating in physical education classes, The Emotional Intelligence Inventory along with the standardized physical fitness tests were used to collect data. The t-tests and ANOVA further showed that athletes possessed better EI than non athletes in all aspects of self awareness, empathy and interpersonal sensitivity. Also, the government school athletes reported lower EI than the public school athletes indicating how institutional environments play out in EI. That is why the present research concerns sports as an opportunity to develop EI pointing at the promotion of teamwork, discipline, and stress regulation. This study suggests that effective implementation of sports based training in education is useful to improve overall student’s quality.